SOME OBSERVATIONS ON THE USE OF CLASSICAL SYRIAC IN THE LATE TWENTIETH CENTURY - Brock, Sebastian P. 1938- (1989)
SEBASTIAN P. BROCK; SOME OBSERVATIONS ON THE USE OF CLASSICAL SYRIAC IN THE LATE TWENTIETH CENTURY*, Journal of Semitic Studies, Volume XXXIV, Issue 2, 1 Octobe